A Clinical Study to Evaluate the Efficacy of Patoladi Kwatha along with Navaka Guggulu in Polycystic Ovarian Syndrome with special reference to Artavakshaya (International Journal of Ayurveda and Pharma Research, 2023)
Polycystic ovarian syndrome is a systemic, endocrinal and also a metabolic disorder and it is the most common cause of hyperandrogenic chronic anovulation occurring in reproductive age group. Acharya Kashyapa mentioned about Pushpagni jataharini, it bears some resemblance with symptoms of PCOS. But most of the symptoms seen in this disease are related to the Artavavaha srotas. The factors which vitiate Kapha, Vata, and Meda have a considerable role in this disease. So here an attempt has been made to work on the efficacy of Patoladi Kwatha along with Navaka Guggulu in PCOS, as it is mentioned that Patoladi Kwatha is Hitakara for Andadhara roga in Andadhaara roga chikitsa adhyaya of Bhaishajya Ratnavali. Methods: Convenient sampling and interventional analytical experimental study were carried out for 30 patients fulfilling the diagnostic criteria for PCOS. Group A with Patoladi kwatha along with Navaka guggulu and Group B with Varunadi kwatha along with Kanchanara guggulu were given for 60 days and 30 days follow up also done by drug free period. Results: In group A, 60% had moderate improvement and 40% had marked improvement from PCOS. In group B, 46.66% had moderate improvement and 53.33% had minor improvement from PCOS. Conclusion: Polycystic Ovarian syndrome, the term itself indicates more than one symptom and hence possibility for multisystem involvement with ovarian dysfunction. The factors which vitiate Kapha, Vata, and Meda have a considerable role in this disease. So, to treat this, drugs should have the properties like Ushna, Teekshna guna, Kapha vata hara and Medahara or Lekhaniya karma. The Patoladi kwatha along with Navaka guggulu is having all these properties. Thus, Patoladi kwatha along with Navaka guggulu is superior to Varunadi kwatha along with Kanchanara guggulu for the treatment of PCOS w.s.r to Artavakshaya.